RETHINKING LAND REGISTRATION IN XXI CENTURY SERBIA - Živković, Miloš D. (Pravni zapisi, 2022)
In the late XX century, Serbia changed its system of land registration from the land books, that were outdated and neglected during the socialist era, to unified cadaster, the REC. Due to historical circumstances and construction of the REC system, lawmakers had to resort to unorthodox solutions to achieve the desired level of legal security. Because of unifying records of different nature (factual and legal), the REC needed to rethink the principle of legality and include the public notaries and courts in its implementation. Modernizing the registry meant that information technologies were used very broadly, making the shift to a fully electronic procedure of registration one of the main policy goals. This enabled introduction of the principle of registration by official duty, for the records to always be up to date. Mechanisms of protecting legal security provided by the registry do not function for objects under construction because they are not registered until the construction is completed. Therefore, the last unorthodox novelty was introduced: registration of buildings and apartments under construction.